Recent advances in autoimmune pancreatitis - Kamisawa, Terumi; Tabata, Taku; Hara, Seiichi; Kuruma, Sawako; Chiba, Kazuro; Kanno, Atsushi; Masamune, Atsushi; Shimosegawa, Tooru (Frontiers in Physiology, 2012)
It is now clear that are two histological types (Type 1 and Type 2) of autoimmune pancreatitis (AIP). The histological pattern of Type-1 AIP, or traditional AIP, is called lymphoplasmacytic sclerosing pancreatitis. The histological pattern of Type-2 AIP is characterized by neutrophilic infiltration in the epithelium of the pancreatic duct. In general, Type-2 AIP patients are younger, may not have a male preponderance, and rarely show elevation of serum IgG4 compared with Type-1 AIP patients. Unlike Type-1 AIP patients, Type-2 AIP patients rarely have associated sclerosing diseases, but they are more likely to have acute pancreatitis and ulcerative colitis. Although Type-2 AIP is sometimes observed in the USA and Europe, most AIP cases in Japan and Korea are Type-1. The international consensus diagnostic criteria for AIP comprise 5 cardinal features, and combinations of one or more of these features provide the basis for diagnoses of both Type-1 and Type-2 AIP. Due to the fact that steroid therapy is clinically, morphologically, and serologically effective in AIP patients, it is the standard therapy for AIP. The indications for steroid therapy in AIP include symptoms such as obstructive jaundice and the presence of symptomatic extrapancreatic lesions. Oral prednisolone (0.6 mg/kg/day) is administered for 2-4 weeks and gradually tapered to a maintenance dose of 2.5-5 mg/day over a period of 2-3 months. Maintenance therapy by low-dose prednisolone is usually performed for 1-3 years to prevent relapse of AIP.